Pengaruh Daya Tarik Promosi, Presepsi Kemanfaatan dan Presepsi Kemudahan Terhadap Minat Penggunaan E-Wallet (Dana) Pada Mahasiswa Di Yogyakarta The Influence of Promotional Appeal, Perceived Usefulness, and Perceived Ease of Use on the Interest in Using E - Rado, Elivia; Widiyanti, Anik; Sari, Eliza Oktaliana; Melati, Sunti (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2025)
This research is motivated by the rapid growth of financial technology (fintech) in Indonesia, particularly the increasing popularity of e-wallets as a modern payment method among the public, including university students. Students in Yogyakarta, as part of the digital generation, represent a potential user segment in adopting digital wallet applications such as DANA. Therefore, it is important to conduct research to gain a deeper understanding of the factors that influence their interest in using such services. This study aims to analyze the influence of promotional appeal, perceived usefulness, and perceived ease of use on students’ interest in using the DANA e-wallet in Yogyakarta.